Chiari Malformation-I with Syringomyelia: A Non-specific Presentation and Surgical Consideration - Maharjan, Jemesh S; Shrestha, Pranaya; Chandra, Avinash; Rajbhandari, Pravesh; Acharya, Samir; Shrestha, Resha; Bhattarai, Robin; Pant, Basant (Nepal Journal of Neuroscience, 2016)
Chiari Malformation-I is a congenital disorder characterized by the anatomical defect of the base of skull with tonsillar herniation (≥5 mm) below the foramen magnum, which is detected on MRI. It has a diverse range of symptoms with non-specific presentation leading to the chances of misdiagnosis and untimely recognition of the disorder. Syringomyelia is the most common result of Chiari-I. The selection of surgical or non-surgical management depends upon the patient symptoms and the presence of absence of Syringomyelia. The objective of this case report is to give a broad perspective on Chiari Malformation-I from the symptoms and clinical findings obtained in a patient with Syringomyelia associated with Chiari Malformation-I and to discuss about the different surgical options as well as the psychological support required for the management of the condition. Nepal Journal of Neuroscience. Vol. 13, No. 2, 2016, Page: 105-108